ASEAN Guidelines for Agroforestry Development set to revolutionize land use in Southeast Asia - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
Ministers on Agriculture and Forestry of the Association of South East Asian Nations endorse Guidelines for Agroforestry Development, developed by ICRAF. The adoption of the guidelines paves the way for implementation to restore degraded landscapes, improve food security and livelihoods, enhance farmers resilience and meet nationally determined contributions to climate-change targets.